Comparison of Active & Conservative Management of Post-Term Pregnancy: A Quasi- Experimental Study (Medical Forum Monthly, 2024)
Objective: To compare the maternal and perinatal outcomes of prolonged pregnancy between active and conservative group.Study Design: Quasi experimental study.Place and Duration of Study: This study was conducted at the Department of Obstetrics / Gynaecology Unit-1, Mother and Child Health Centre, Pakistan Institute of Medical Sciences, Islamabad from March 2003 to Feb. 2004.Materials and Methods: There were one hundred cases, fifty in each group with a technique of convenient sampling. Women with uncomplicated pregnancies at ³ 41 weeks &£ 43 weeks were included, excluding the women with obstetrical and medical risks. Women were divided into active and conservative groups. Active group was induced with PGE2(Prostaglandin-E2) and conservative group had follow ups twice weekly till 43 weeks. Pregnancy was intervened during this period if CTG (cardiotocogram) was abnormal, BPP (biophysical profile) was 6/8 with AFI (amniotic fluid index)£ 5 and/or woman complained of decreased fetal movements. Maternal outcome measures included duration of labor and mode of delivery and fetal/neonatal outcome measures included intra-partum fetal distress, one and five minutes Apgar score and NICU (neonatal intensive care unit) admissions.Results: Comparison of both groups management showed that mean duration of labour in active group was prolonged than that of conservative group (p =0.001). Interventional deliveries rate was high in active group than conservative group with p value significant statistically. Comparison of intra-partum fetal distress, neonatal morbidity including 1 minute, 5 minute Apgar score and admissions to NICU in both groups was not statistically significant. There was no perinatal mortality in both groups.Conclusion: Active management of prolonged pregnancy increases the maternal morbidity without improving perinatal outcome.